2011
DOI: 10.1021/jp207333y
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermal Effects on the Charge Transport of Core-Twisted Chlorinated Perylene Bisimide Semiconductors

Abstract: We acknowledge grants from MIUR: ex 60% and PRIN Project 2008 JKBBK4 "Tracking ultrafast photoinduced intra-and intermolecular processes in natural and artificial photosensors". Whe are indebted to the referees for their comments and suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 59 publications
(109 reference statements)
4
42
0
Order By: Relevance
“…68 However, the presence of the ethynylene bridges in (ArCC) 2 Ph derivatives substantially lowers λ i to values comparable to those reported for the above mentioned reference compounds (see Table 1). The decrease of λ i is closely related to the change in the shape of the LUMO, which becomes completely delocalized for (ArCC) 2 Tz (see Figure 1 for (PhCC) 2 Tz).…”
Section: Resultssupporting
confidence: 68%
“…68 However, the presence of the ethynylene bridges in (ArCC) 2 Ph derivatives substantially lowers λ i to values comparable to those reported for the above mentioned reference compounds (see Table 1). The decrease of λ i is closely related to the change in the shape of the LUMO, which becomes completely delocalized for (ArCC) 2 Tz (see Figure 1 for (PhCC) 2 Tz).…”
Section: Resultssupporting
confidence: 68%
“…The Monte Carlo method is a stochastic approach to tackle mathematical problems which are analytically or numerically hard to handle. The kinetic Monte Carlo method, which allows for the simulation of the time evolution of a system, is frequently used to study charge and exciton transport in organic solids. Instead of solving the master equation directly in order to obtain the (probability) distribution, one can also solve this equation stochastically.…”
Section: Simulation Of the Dynamicsmentioning
confidence: 99%
“…1) may easily happen. 50,90,91 But for excitons the coupling decays much slower with the distance and a much larger number of dimers gives significant contributions to the transport and one would expect a much weaker trapping effect. Here it is shown that, nevertheless, the effect is important for exciton diffusion as well.…”
Section: A Naphthalenementioning
confidence: 99%